Ảnh hưởng của hội chứng FOMO và việc tiếp xúc với người có ảnh hưởng đến ý định mua hàng: trường hợp sinh viên Đà Nẵng - Đỗ Hương , Thủy; Trần Khánh , Huyền; Nguyễn Thị Mỹ , Tâm; Nguyễn Bùi Minh , Thư; Phan Hoàng , Long (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study contributes to the extant literature by examining the moderating role of Fear of Missing Out (FOMO) in the relationship between influencer exposure and purchase intention while also investigating the effect of FOMO on purchase intention through the mediating roles of psychological factors. Data analysis from 207 survey samples collected from university students in Danang shows that FOMO affects purchase intentions through three mediating variables: anticipated excitement, self-enhancement, and anticipated expense regret. The first two variables strengthen purchase intentions, whereas anticipated expense regret weakens purchase intentions. This study also shows a positive relationship between exposure to influencers and purchase intentions through two mediating variables: desire to mimic and materialism. However, the results do not establish the moderating role of FOMO on the impacts that exposure to influencers has on materialism and purchase intentions. Practical implications of the research results are also discussed.